2022
DOI: 10.1093/jas/skac167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of essential fatty acids in lactating sow diets on sow reproductive performance, colostrum and milk composition, and piglet survivability

Abstract: Mixed parity sows (n=3,451; PIC, Hendersonville, TN; parities 2 through 9) and their litters were used to evaluate the effects of essential fatty acid (EFA) intake on sow reproductive performance, piglet growth and survivability, and colostrum and milk composition. Our hypothesis, like observed in earlier research, was that increasing linoleic acid (LA) and α-linolenic acid (ALA) would improve sow and litter performance. At approximately d 112 of gestation, sows were randomly assigned within parity groups to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Regarding the influence of animal parity, our results demonstrated that primiparous sows had higher milk linoleic acid concentration than multiparous sows. This observation was aligned with literature stating that, without lipid supplementation, sows advance in parity could encounter a negative EFA scenario during their lactation 29 , 33 . Because linoleic acid (C18:2n6c) is a precursor for synthesis of hormones involved in diverse stages of reproduction, dietary EFA supplementation is thus recommended to mature sows 29 , 33 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the influence of animal parity, our results demonstrated that primiparous sows had higher milk linoleic acid concentration than multiparous sows. This observation was aligned with literature stating that, without lipid supplementation, sows advance in parity could encounter a negative EFA scenario during their lactation 29 , 33 . Because linoleic acid (C18:2n6c) is a precursor for synthesis of hormones involved in diverse stages of reproduction, dietary EFA supplementation is thus recommended to mature sows 29 , 33 .…”
Section: Discussionsupporting
confidence: 88%
“…This observation was aligned with literature stating that, without lipid supplementation, sows advance in parity could encounter a negative EFA scenario during their lactation 29 , 33 . Because linoleic acid (C18:2n6c) is a precursor for synthesis of hormones involved in diverse stages of reproduction, dietary EFA supplementation is thus recommended to mature sows 29 , 33 . Lignoceric (C24:0) and behenic acid (C22:0) are very long-chain saturated fatty acids (VLSFA) present in milk of various mammal species 34 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present experiment con rmed that the fatty acid pro le in sow's colostrum was in uenced by the dietary α-GML. Previous studies have shown that the impact of dietary fatty acid composition during the last gestation and lactation on fatty acid pro le of colostrum and milk [7,8]. However, this study is the rst one using α-GML for sow nutrition.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have found that dietary supplementation of fatty acids during late pregnancy and/or lactation can increase the overall litter growth and pig weaning weights [7], reduce body weight loss during lactation and shorten the weaning-to-estrus interval [6]. Furthermore, the type and amount of fat in daily feed rations also affect the sow milk yield and the milk fatty acids pro le [8].…”
Section: Introductionmentioning
confidence: 99%